Ethnic disadvantage in Vietnam: Evidence using panel data - Saurabh Singhal; Ulrik Beck (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This study investigates the ethnic disadvantage in rural Vietnam, focusing on the magnitude of the majority-minority gap and the constraints on ethnic minority households that contribute to the gap. Using a biannual panel dataset spanning the period 2006 - 14, this paper documents large improvements in living standards both for the Kinh majority as well as for the ethnic minorities. However, a significant difference between the Kinh households and the rest persists - and there is no sign that the gap is closing. Examining the sources of income shows that non-Kinh households are less likely to diversify into high-yielding non-farm activities. Non-Kinh households have lower quality agricultural land, lower rates of ownership certificates, face more problems in producing and selling their agricultural products, and have worse access to credit. However, the locational disadvantage of the non-Kinh households has substantially declined over time. Finally, the data allows us to examine intra-minority dynamics and we find differences among the various non-Kinh minorities along spatial, ethnic, and linguistic lines.
Keywords: 330; ethnic disadvantage; Vietnam